Clinical and prognostic value of parameters of cytokine regulation in oxygen-dependent patients with the coronavirus disease COVID-19 - Riabokon, O. V.; Cherkaskyi, V. V.; Riabokon, Yu. Yu.; Shcherbyna, R. O.; Рябоконь, Олена Вячеславівна; Черкаський, Володимир Васильович; Рябоконь, Юрій Юрійович; Щербина, Роман Олександрович (Запорізький державний медико-фармацевтичний університет, 2023)
Aim of the work is to find out the clinical and prognostic significance of cytokine regulation parameters in oxygen-dependent patients with COVID-19 coronavirus disease in dynamics of the disease. Material and methods. 78 oxygen-dependent patients with COVID-19 aged from 52 to 84 years were examined. All patients were examined and treated in accordance with the regulations in force at the relevant time. The patients were divided into groups: I group – 38 patients who recovered; II group – 40 patients with fatal outcome of the disease. In the blood serum of patients with COVID-19 and 20 healthy individuals, were determined by enzyme immunoassay the content of interleukin (IL) IL-2 (Elabscience, USA), IL-4 (Affymetrix eBioscience, Austria), IL-6 (Invitrogen, Austria), monocyte chemotactic protein-1 (MCP-1) (Elabscience, USA). Statistical processing was performed in the Statistica 13 for Windows program (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. The content of IL-2 in the blood serum of oxygen-dependent patients with COVID-19 of both groups was significantly higher (p < 0.001) than in healthy individuals. IL-2 content was higher in patients of II group (p < 0.001) than in patients of I group. In dynamics, a further increase in content of IL-2 was noted in patients of the II group (р < 0.05). The diagnostic significance has been established of the increased level of IL-2 in assessing the high probability of the development of a fatal outcome of the disease during hospitalization (AUC = 0.698, p = 0.030) and in the dynamics of treatment (AUC = 0.745, p = 0.015). Мета роботи – з’ясувати клініко-прогностичне значення параметрів цитокінової регуляції в кисневозалежних хворих на коронавірусну хворобу COVID-19 у динаміці хвороби. Матеріали та методи. У дослідження залучили 78 кисневозалежних хворих на COVID-19 віком від 52 до 84 років. Усі хворі обстежені, отримали лікування згідно з чинними на час дослідження протоколами. Хворих поділили на групи: I – 38 пацієнтів, які одужали; II – 40 осіб із летальним наслідком хвороби. У сироватці крові хворих на COVID-19 і 20 здорових осіб методом імуноферментного аналізу визначали вміст інтерлейкіну IL-2 (Elabscience, USA), IL-4 (Affymetrix eBioscience, Austria), IL-6 (Invitrogen, Austria), моноцитарного хемотактичного протеїну-1 (MCP-1) (Elabscience, USA). Статистично результати опрацювали в програмі Statistica 13 for Windows (StatSoft Inc., No. JPZ804I382130ARCN10-J). Результати. Вміст IL-2 у сироватці крові кисневозалежних хворих на COVID-19 обох груп значно вищий (р < 0,001), ніж у здорових. У хворих ІІ групи вміст IL-2 вищий (р < 0,001), ніж у пацієнтів І групи. У динаміці в хворих ІІ групи визначали зростання вмісту IL-2 (р < 0,05). Встановили діагностичну значущість підвищення IL-2 в оцінці високої ймовірності настання летального наслідку хвороби і при госпіталізації (AUC = 0,698, p = 0,030), і в динаміці лікування (AUC = 0,745, p = 0,015).
Клініко-прогностичне значення параметрів цитокінової регуляції в кисневозалежних хворих на коронавірусну хворобу COVID-19
Riabokon O. V. - ORCID ID: 0000-0002-7394-4649; Cherkaskyi V. V. - ORCID ID: 0000-0003-2959-8803; Riabokon Yu. Yu. - ORCID ID: 0000-0002-2273-8511; Shcherbyna R. O. - ORCID ID: 0000-0002-9742-0284.
Keywords: coronavirus disease; COVID-19; viral infection; cytokines; cytokine storm; prognosis; коронавірусна хвороба; COVID-19; вірусна інфекція; цитокіни; итокіновий шторм; прогноз